Schaum's outlines of theory and problems of numerical analysis - Scheid, Francis (Schaum's outline series. Schaum's outline series in mathematics, 1989)
If you want top grades and thorough understanding of numerical analysis, this powerful study tool is the best tutor you can have! It takes you step-by-step through the subject and gives you accompanying related problems with fully worked solutions. You also get additional problems to solve on your own, working at your own speed. (Answers at the back show you how you're doing.) Famous for their clarity, wealth of illustrations and examples-and lack of dreary minutiae-Schaum's Outlines have sold more than 30 million copies worldwide. This guide will show you why!